The acute effect of upper extremity plyometric training - Lin, C.-T.; Chen, C.-H.; Hsieh, H.-S.; Tu, J.-H.; Huang, C.-F. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to probe the acute effect of the performance of upper extremity muscle groups after the plyometric training intervention. The participants were 13 healthy male college students. The force transducers (300kg, 200 Hz) and EMG sensor (1000 Hz) were taken to diagnose the acute effects of strength and muscle activation done by upper extremity pre and post plyometric training (load :24kg, 12 repetiiion times Iset, 3 set), and pair t-test was taken to test the significance(a=.05). The result showed that the strength after the upper extremity plyometric training intervention obviously had decreased 8% (p<.05), and the upper extremity maximum voluntary contraction [MVC] had increased 26% (pc.05). The intervention of upper extremity plyometric training could make the muscle tired.